2021
DOI: 10.3390/plants10102131
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Is the Main Driver of Weed Assemblages in Field Margins but Is Outperformed by Crop Competition in Field Cores

Abstract: Weeds are considered a major pest for crops, and as such have been intensively managed by farmers. However, weeds, by providing resources, also support farmland biodiversity. The challenge for sustainable weed management is therefore to maintain weed diversity without compromising crop production. Meeting this challenge requires determining the processes that shape weed assemblages, and how agricultural practices and landscape arrangement affect them. In this study, we assess the effects of crop competition on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Local management seems to play a major role in the conservation of arable plant communities in the study area. Consistently, previous evidence showed that management factors like crop height, tillage depth, preceding crop, or the overall intensity of management are of primary importance in determining species richness, composition, or both (Fried et al 2008;Pál et al 2013;Berquer et al 2021). The restrained effects of landscape features allow us to confirm that agricultural practices, rather than the surrounding landscape, should be the focus for the conservation of arable plant diversity, as previously highlighted on a local scale (Armengot et al 2011).…”
Section: Implications For Arable Plant Diversity Conservation and Res...supporting
confidence: 87%
See 1 more Smart Citation
“…Local management seems to play a major role in the conservation of arable plant communities in the study area. Consistently, previous evidence showed that management factors like crop height, tillage depth, preceding crop, or the overall intensity of management are of primary importance in determining species richness, composition, or both (Fried et al 2008;Pál et al 2013;Berquer et al 2021). The restrained effects of landscape features allow us to confirm that agricultural practices, rather than the surrounding landscape, should be the focus for the conservation of arable plant diversity, as previously highlighted on a local scale (Armengot et al 2011).…”
Section: Implications For Arable Plant Diversity Conservation and Res...supporting
confidence: 87%
“…However, landscape effects were mainly observed in field margins, while the role of management prevails in field cores (Kovács-Hostyánszki et al 2011). In fact, landscape can be a source of species in field edges, but the features of plant communities in field cores are mainly determined by crop competition and management (Gonthier et al 2014;Berquer et al 2021).…”
Section: Drivers Of α-Diversity Species Composition and β-Diversitymentioning
confidence: 99%
“…For instance, Guerrero et al (2014) found that weed species richness in Spain decreased linearly with field-level intensification, but remained constant at the landscape level. However, Berquer et al (2021), focusing at a resolution under 1 km, found the opposite pattern, with field margin communities showing a greater influence of landscape than agricultural practices. Concepción et al (2012) revealed that extensive farming has a weaker positive impact on weed diversity at the field center and inner field edge when the landscape is less diversified within a 500 m radius.…”
Section: Introductionmentioning
confidence: 92%
“…For example, weed species’ richness within winter wheat crops in Spain was found to decrease linearly with field-level intensification, while remaining constant at the landscape-level (Guerrero et al, 2014). However, field margin communities may be subjected to a greater influence of landscape than agricultural practices (as found by Berquer et al (2021) at a scale lower than 1 km), in contrast to what happens within agricultural fields. Concepción et al (2012) revealed that extensive farming has a weaker positive impact on weed diversity in field center and inner field edge when the landscape is too simple within a 500 m radius.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to keep in mind that increasing the competitive performance of crops against weeds by combining management practices that are unfavourable for weeds with varietal development for these practices, as espoused here, is only one aspect of ecological weed management. It will be most successful if combined with weed management strategies at the plant community and landscape level (Berquer et al, 2021; MacLaren et al, 2020; Mahaut et al, 2019) as well as other factors related to sustainability (e.g., Storkey & Neve, 2018).…”
Section: Two Approaches To Improving Weed Suppression By Cropsmentioning
confidence: 99%